Health Education-Based Group on Self-care Adherence among Patients with Diabetes Mellitus in Cendrawasih Public Health Center, Makassar City - Hasniati, Hasniati; Harbaeni, Harbaeni; Yusuf, Saldy; Masriadi, Masriadi (International Journal of Nursing and Health Services (IJNHS), 2023)
Background: Self-care is crucial strategy to improve and maintain health condition among diabetes patients. However, most type 2 DM patients are disobedient in carrying out self-care. Objective: The study aimed to examine the effect of health education on self-care adherence among patients with diabetes mellitus in Cendrawasih Public Health Center, Makassar city. Method: A quantitative study with pre-experimental approach, two group, pretest and posttest design were applied in this study. Thirty-six diabetes mellitus patients were involved in this study using the total sampling technique since limited number of patients in this Public Health Center. We divided into the experimental group (n=18) and the control group (n=18). The Wilcoxon test was used to analyzed the data.  Result: The results found that there are significantly difference on self-care adherence among type 2 diabetes mellitus before and after receiving the health education with p-value <.05. Conclusion: The health education was effective to improve the understanding of diabetes patients who carry out the self-care in maintaining the self-care. Recommendation: Further study need to apply the wide of study using the Randomized Control Trial (RCT) to ensure the effectiveness of health education using varied of strategy on health outcomes